Muslim Tionghoa Kota Bogor: Studi Kasus Partisipasi Politik pada Pemilu dan Pilpres Tahun 2004: Chinese Muslims in Bogor City: A Case Study of Political Participation in the 2004 Legislative and Presidential Elections - Mahrus Mahrus (Fenomena, 2007)
The political dynamics of Chinese Muslims in post-Suharto Indonesia reflect a complex intersection of ethnic and religious identity, particularly during democratic events such as the 2004 General and Presidential Elections. This study explores the political participation of Chinese Muslims in Bogor City, a minority group that remains largely invisible within local political structures. The research aims to analyse the extent and forms of their political engagement and to identify whether ethnic or religious factors primarily influence their voting behaviour. A qualitative approach was employed, combining historical and ethnographic methods, including participant observation, in-depth interviews, life story analysis, and documentary review. The findings reveal that the political participation of Chinese Muslims in Bogor falls into the minimal participation category, characterised almost exclusively by voting on election days. No individual or collective political actions, such as campaigning or joining political discussions, were observed. This passivity is attributed to their relatively small population, the absence of prominent community leaders, and their predominantly lower-middle-class socioeconomic background. Although some key figures exist, they remain reluctant to publicly identify themselves. In conclusion, while Chinese Muslims in Bogor exercise their voting rights, their broader political engagement is limited. Recommendations include the need for communal organisation and leadership development to enhance future participation. Dinamika politik Muslim Tionghoa di Indonesia pasca-Suharto menunjukkan persinggungan kompleks antara identitas etnis dan agama, terutama dalam peristiwa demokrasi seperti Pemilu dan Pilpres 2004. Penelitian ini mengeksplorasi partisipasi politik Muslim Tionghoa di Kota Bogor, kelompok minoritas yang masih belum tampak dalam struktur politik lokal. Tujuan penelitian ini adalah menganalisis bentuk dan tingkat partisipasi politik mereka serta mengidentifikasi apakah faktor etnis atau agama yang lebih memengaruhi perilaku memilih. Penelitian ini menggunakan pendekatan kualitatif dengan metode historis dan etnografi, melalui observasi terlibat, wawancara mendalam, analisis riwayat hidup, dan studi dokumen. Hasil penelitian menunjukkan bahwa partisipasi politik Muslim Tionghoa di Bogor termasuk dalam kategori partisipasi minimalis, yang hanya diwujudkan dengan pemberian suara saat pemungutan suara. Tidak ditemukan bentuk partisipasi individu atau kolektif lainnya, seperti kampanye atau diskusi politik. Hal ini disebabkan oleh jumlah populasi yang relatif sedikit, tidak adanya tokoh dominan, serta latar belakang ekonomi menengah ke bawah. Meskipun terdapat beberapa tokoh kunci, mereka masih enggan mengungkapkan identitasnya secara terbuka. Kesimpulannya, Muslim Tionghoa Bogor menggunakan hak pilihnya, tetapi keterlibatan politik yang lebih luas masih sangat terbatas. Rekomendasi penelitian ini adalah perlunya wadah organisasi dan pengembangan kepemimpinan untuk meningkatkan partisipasi politik ke depan.